Transcatheter aortic valve replacement without previous conduction disturbances: The importance of preventing iatrogenic pacemaker implantation. Issue 5 (15th April 2020) - Tarantini, Giuseppe; Fabris, Tommaso
Key Points: Transcatheter aortic valve replacement (TAVR) patients given pacemakers operating in mandatory DDD mode had more ventricular pacing, heart failure hospitalization, and mortality compared with AAI‐DDD or VVI modes. AV conduction disturbances are often transient after TAVR. Minimizing ventricular pacing where possible avoids the risk of pacemaker‐induced cardiomyopathy. Pacemaker specialists should be consulted for any TAVR patient with mild rhythm abnormalities given the high incidence of AV block. Careful stratification of patients with conduction disturbances during TAVR may help identify the patients who will require an early permanent pacemaker implantation strategy.